Comprehensive assessment of the long-term energy harvest capabilities for PV systems with different tilt angles: Case study in Taiwan. (December 2018) - Kuo, Kun-Chang; Liao, Min-Sheng; Wang, Jen-Cheng; Lee, Yeun-Chung; Huang, Chen-Kang; Chou, Cheng-Ying; Liu, Cheng-Yue; Hsu, Hsuan-Hshiang; Chen, Po-Han; Jiang, Joe-Air
Abstract: This paper presents an overview of assessments of the long-term energy harvest capabilities of different photovoltaic (PV) systems. Based on semiconductor theory, an effective assessment approach is developed which can be used for evaluation of the ratios of energy harvested by different PV systems at various latitudes. The proposed approach makes evaluation of the theoretical and the benefits of their business applications easy to assess. To test the applicability of the proposed approach, single-axis sun-tracking type (SASTT), dual-axis sun-tracking type (DASTT), and fixed-type (FT) PV systems with various tilt angles, all with a rated power capacity of 3.68 kW, were installed in northern Taiwan (latitude of 24.92°) and experiments were conducted over a one year period. The prediction errors between theoretical simulations and long-term field verifications were less than 4%. The assessment results indicate that FT PV systems with a smaller tilt angle would be a better choice for installation in Taiwan. This finding overturns the current installation guidelines in Taiwan, i.e., FT PV systems should be installed with a tilt angle of 23.5°. The proposed assessment approach can provide data for objective comparisons of any type of PV system and offers a valuable reference for PV system installers before they invest time, money, and energy for installation. Highlights: A assessment of the energy harvest for fixed and sun-tracking type PV systems. It is developed based on semiconductor theory and solar trajectory tracking method. The field data were used to evaluate the energy harvest for the several PV systems. The power increment estimation and prediction error for PV systems are accurate. It can provide the objective comparison and significant referential for PV systems.